(untitled) (Faridpur Medical College Journal, 2013)
Upper GI bleeding is a common medical emergency with a significant mortality, outcome of which depends upon the cause, appropriate and early intervention in a specialized center. This study was carried out to see the outcome of patient with Upper GI haemorrhage. Fifty cases with episode of upper gastrointestinal haemorrhage, admitted into medicine units of Faridpur Medical College Hospital from January 2011 to December 2011, were studied. Duodenal ulcer was the commonest cause of haematemesis and melaena followed by oesophageal varices, gastric ulcer and erosive gastritis. The peak incidence was among 35 to 45 years of age. Over all male female ratio was 4.55:1 but in case of duodenal ulcer it was 9:1. During hospital stay recurrent bleeding was noted in 10% of patients and during subsequent follow up it was 10% of the total and 50% in case of variceal bleeding group. Over all hospital mortality was 4% . DOI: http://dx.doi.org/10.3329/fmcj.v8i1.16891 Faridpur Med. Coll. J. 2013;8(1): 15-17